Video documental sobre la incidencia del robo de la Custodia en la subjetividad de los habitantes de Riobamba. - Vallejo Peñafiel, Juan Danilo (2013)
The story begins when six robbers who entered the October 13, 2007 at the Museum of Riobamba Conceptas had not the slightest obstacle to take custody of the glass case, did not even need to break a glass only, or disconnect any alarm, nor worried about potential security cameras, nothing protected the room 14, where it was exhibited custody, one of the greatest pieces of economic and historical value to the city of Riobamba. Custody theft, crown, scepter and robe of the Virgin of Sicalpa reveals a total lack of prevention, care and safety. It is not enough the will of the religious or religious in convents and churches, where through product shown concern and impact it had on people.